2004
DOI: 10.1007/s00234-004-1213-3
|View full text |Cite
|
Sign up to set email alerts
|

How does the blood leave the brain? A systematic ultrasound analysis of cerebral venous drainage patterns

Abstract: The internal jugular veins are considered to be the main pathways of cerebral blood drainage. However, angiographic and anatomical studies show a wide anatomical variability and varying degrees of jugular and non-jugular venous drainage. The study systematically analyses the types and prevalence of human cerebral venous outflow patterns by ultrasound and MRI. Fifty healthy volunteers (21 females; 29 males; mean age 27+/-7 years) were studied by color-coded duplex sonography. Venous blood volume flow was measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
160
1
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 177 publications
(176 citation statements)
references
References 15 publications
11
160
1
2
Order By: Relevance
“…When humans are upright, the predominant venous drainage of the brain is via the vertebral venous plexus, rather than the internal jugular vein. [12][13][14][15] In contrast, the jugular veins are the dominant drainage for the supine patient. 12,15 One described major connecting pathway is the anterior condylar confluence, which has been shown to have connections between the jugular bulb and the anterior, lateral, and posterior condlylar veins, and may have a significant role in the postural redirection of flow.…”
Section: Discussionmentioning
confidence: 99%
“…When humans are upright, the predominant venous drainage of the brain is via the vertebral venous plexus, rather than the internal jugular vein. [12][13][14][15] In contrast, the jugular veins are the dominant drainage for the supine patient. 12,15 One described major connecting pathway is the anterior condylar confluence, which has been shown to have connections between the jugular bulb and the anterior, lateral, and posterior condlylar veins, and may have a significant role in the postural redirection of flow.…”
Section: Discussionmentioning
confidence: 99%
“…However, several authors showed that venous outflow may be influenced by posture and anatomic variability (14,54), raising the potential for nonjugular venous drainage to result in an underestimation of vasoactive agents. Unfortunately, these authors (14, 54) did not perform angiographic studies; however, Doepp et al (14) reported that the internal jugular veins were the main source of venous drainage in 72% of their supine healthy volunteers.…”
Section: Methodological Considerations and Limitationsmentioning
confidence: 99%
“…The extracted NT-CNP was added to primary rabbit antiserum (J39) raised against NT-proCNP-(1-15) (1:6,000 dilution, 100 l antiserum/assay tube). Peptide standards were made from synthetic human proCNP- (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15), with the purity data supplied by the manufacturer (Chiron Technologies) taken into account. Within-and between-assay CVs were 6.0% and 7.9%, respectively.…”
Section: Analytic Measurementsmentioning
confidence: 99%
“…28,82 In a systematic ultrasonography and MRI analysis of the types and prevalence of human cerebral venous outflow, it was shown that there is predominantly jugular drainage in 72% of healthy volunteers. 26 In 22% the jugular drainage equals the nonjugular drainage, and in 6% the drainage pattern is nonjugular. These findings suggest that in the general population there are variations in the anatomy of cranial venous outflow.…”
Section: Pathophysiology Of Cerebral Venous Overdrainagementioning
confidence: 99%
“…26,36,63 A marked increase in central venous pressure, such as any Valsalva maneuver, completely reopens the internal jugular veins. 26 In an ultrasonography study of the postural dependency of venous outflow, it was shown that blood flow in the internal jugular veins decreases from 700 ml/min in the supine position to 70 ml/min at 90° elevation while flow in the vertebral veins is increased from 40 to 210 ml/min. 85 Total venous outflow declines from 740 to 280 ml/min from 0° to 90°, with the largest decrease at 15°.…”
Section: 8294mentioning
confidence: 99%